KAJIAN PERENCANAAN BISNIS PADA USAHA KECIL DAN MENENGAH (STUDI PADA USAHA PERCETAKAN TELA PRES, KERAJINAN BESI PUTIH, DAN PENGRAJIN OVEN DI DARUBA KABUPATEN PULAU MOROTAI) - Rahmat Sabuhari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
Abstract Micro, Small and Medium Enterprises (SMEs) is a business that is managed by the community that continues to grow and evolve in tune with the growth ofthe nation's economy. This study aims to determine the model of businessplanning, implementation planning, and problems that hinder business statsfaced by the MSMEs in the District of Morotai Island.The method used in this research is qualitative research, interviewing some ofthe informants as respondents. The results showed that the white metalcraftsman and kitchen tools lack an understanding of business planning sothat business is less developed, businessmen will tela pres deeply understandbusiness planning to sustain their business, not their long-term businessobjectives, the employee also can not implement the plan with the businessrancana well, on the other hand employees can complement each other's work,if an employee is absent. The things that cause against less concerned forentrepreneurs to business planning is always ignored.Finally expected on craftsmen or business owners to be able to make a formalplanning, because it can be useful in the coming period, as well as adescription of the work to employees or members of the craftsmen will workdikerajakannya, and the District Government Morotai Island, presumably canhelp the SME my head in terms of the management training and businessplanning for entrepreneurs to have skills in business planning.